The Potential Impact of SGLT2-I in Diabetic Foot Prevention: Promising Pathophysiologic Implications, State of the Art, and Future Perspectives—A Narrative Review - Giuseppe Miceli; Maria Grazia Basso; Andrea Roberta Pennacchio; Elena Cocciola; Chiara Pintus; Mariagiovanna Cuffaro; Martina Profita; Giuliana Rizzo; Mariachiara Sferruzza; Antonino Tuttolomondo (Medicina)
The impact of diabetic foot (DF) on the healthcare system represents a major public health problem, leading to a considerable clinical and economic burden. The factors contributing to DF’s development and progression are strongly interconnected, including metabolic causes, neuropathy, arteriopathy, and inflammatory changes. Sodium–glucose cotransporter 2 inhibitors (SGLT2-i), novel oral hypoglycemic drugs used as an adjunct to standard treatment, have recently changed the pharmacological management of diabetes. Nevertheless, data about the risk of limb amputation, discordant and limited to canagliflozin, which is currently avoided in the case of peripheral artery disease, have potentially discouraged the design of specific studies targeting DF. There is good evidence for the single immunomodulatory, neuroprotective, and beneficial vascular effects of SGLT2-i. Still, there is no clinical evidence about the early use of SGLT2-i in diabetic foot due to the lack of longitudinal and prospective studies proving the effect of these drugs without confounders. This narrative review aims to discuss the main evidence about the impact of SGLT2-i on the three complications of diabetes implicated in the development of DF, the state of the art, and the potential future implications.